2010
DOI: 10.1063/1.3531742
|View full text |Cite
|
Sign up to set email alerts
|

Axial dispersion in segmented gas-liquid flow: Effects of alternating channel curvature

Abstract: The effects of channel curvature on the axial dispersion in segmented gas-liquid flows are studied computationally in a two-dimensional setting using a finite-volume/front-tracking method. Passive tracer particles are used to visualize and quantify the axial dispersion. The molecular diffusion is modeled by random walk of tracer particles. It is found that there is significant axial dispersion in serpentine channels even in the absence of molecular diffusion. The lubricating thin liquid layer that persists on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 36 publications
3
11
0
Order By: Relevance
“…According to the twofilm theory, the concentration of CO 2 in the main body of the liquid slug is obviously reduced due to the enhancement of the turbulence degree of the fluid by the secondary flow. Thus, the mixing of the newly added solute CO 2 in the main body of the liquid slug is consistent with the mixing law of the solute in the liquid slug under the secondary flow proposed by Muradoglu et al 26 Eventually, the shrinking rate of the bubble can be expressed by i k j j j j j y…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…According to the twofilm theory, the concentration of CO 2 in the main body of the liquid slug is obviously reduced due to the enhancement of the turbulence degree of the fluid by the secondary flow. Thus, the mixing of the newly added solute CO 2 in the main body of the liquid slug is consistent with the mixing law of the solute in the liquid slug under the secondary flow proposed by Muradoglu et al 26 Eventually, the shrinking rate of the bubble can be expressed by i k j j j j j y…”
Section: Resultssupporting
confidence: 85%
“…where A s is the area of the liquid slug and A h is the area of the liquid layer that leaks through the outer film in the halfperiod. 26 Period refers to the periodic change of the liquid film when bubbles pass through the bent channel, as shown in Figure 3C. In the experiment, the liquid film undergoes a similar change for four consecutive curves, which is defined as a bubble change period.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors identified three characteristic dispersion regimes, depending on the Peclet number. In a follow-up paper, Muradoglu (2010) investigated the effects of alternating channel curvature and found that the axial dispersion in a serpentine channel is enhanced as compared with a straight one. Wörner et al (2007) evaluated the diffusion-free liquid phase residence time distribution in Taylor flow through a square minichannel from 3D PLIC-VOF computations.…”
Section: Mixing and Dispersionmentioning
confidence: 97%